The implementation of pictures media to improve paragraph writing skill - Siti Sulastri (Universitas PGRI Madiun, 2019)
The main objectives of the research are: (1) to identify whether pictures can improve students’ paragraph writing skill for the tenth graders of Senior High School in SMAN 1 Magetan; (2) to identify the students’s motivation when the pictures are used to teach paragraph writing skill for the tenth graders of Senior High School in SMAN 1 Magetan in academic year 2018/2019. The Research was carried out at SMAN 1 Magetan, East Java, in second semester from January 2019 to May 2019. The subjects of the research are 34 students of grade X. MIPA -1 consisting of 14 boys and 20 girls. The data were obtained from several techniques: test, observation, interview, questioners, and document analysis. To analyze the qualitative data, I used interactive model; while to analyze quantitative data, I applied a descriptive statistics. It is done by comparing the mean of pre-test and post-test. There are some findings of the research which include: pictures can improve students’ paragraph writing skill for the tenth graders of Senior High School in SMAN 1 Magetan. The improvements of paragraph writing skill comprise: (1) writing topic sentence; (2) writing supporting sentences; and (3) using correct grammar and cohesive devices (conjunctions). In addition, the students’ motivation is better when the pictures are used to teach paragraph writing skill for the tenth graders of Senior High School in SMAN 1 Magetan. Based on the result of the research, it can be concluded that applying pictures as media can improve students’ paragraph writing. Therefore, it is recommended that the teachers can use pictures as an effective media to improve the students’ paragraph writing skill.